A predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae): worldwide occurrence datasets - Migeon, Alain; Tixier, Marie-Stéphane; Navajas, Maria; Litskas, Vassilis D.; Stavrinides, Menelaos (My University, 2019)
The predator-prey system Phytoseiulus persimilis Athias-Henriot (Acari: Phytoseiidae) and Tetranychus urticae (Koch) (Acari: Tetranychidae) represents the most studied and the most known system among the Acari. Because of the agronomical importance of the two mite species, a wealth of modelling studies investigated the interactions of the two species at the individual level. However, regional or global level works on this system are lacking, which is impeding the investigation of climate change effects on biological control effectiveness. Here we compile and geo-locate worldwide occurrences for the two species considered, based on literature, collection and field survey data. The datasets presented in this document gather most of the literature records of both species for which locality data were available for geo-referencing (1,037 for T. urticae and 126 for P. persimilis). Geo-located data from collections and field surveys including host-plants are also presented for the first time (322 for T. urticae and 65 for P. persimilis). Phytoseiulus persimilis is also reported for the first time from Kenya and La Martinique.
Keywords: Collection records; Distribution; Host-plant; Literature records; Modelling